2021
DOI: 10.1097/gox.0000000000003608
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Plastic Surgeon Operative Time for DIEP Flap Breast Reconstruction: 2-stage More Efficient than 1-stage?

Abstract: Background: The deep inferior epigastric perforator flap for breast reconstruction is associated with lengthy operative times that remain an issue for plastic surgeons today. The main objective of this study was to determine if a 2-stage deep inferior epigastric perforator flap reconstruction resulted in a shorter total plastic surgeon operative time compared with an immediate reconstruction. Methods: A retrospective chart review was conducted on all patients who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
(30 reference statements)
2
10
0
Order By: Relevance
“…One of the disadvantages of surgically delaying TDAP flaps is that this requires 2 operations, increasing hospital stay and surgical course. However, the total operative time to surgically delay the TDAP flap and reconstruct the unilateral breast with either no concurrent procedures or concurrent capsulectomy only in this series is 313 ± 30 minutes (n = 7 flaps) with 2 surgeons, which is comparable to the total duration of DIEP flap breast reconstruction cases 39,40 . It is well-documented that free flap breast reconstruction often requires access to microsurgical expertise, longer hospital stay, and additional resources for inpatient floor or intensive care unit flap monitoring 41–43 .…”
Section: Discussionmentioning
confidence: 76%
“…One of the disadvantages of surgically delaying TDAP flaps is that this requires 2 operations, increasing hospital stay and surgical course. However, the total operative time to surgically delay the TDAP flap and reconstruct the unilateral breast with either no concurrent procedures or concurrent capsulectomy only in this series is 313 ± 30 minutes (n = 7 flaps) with 2 surgeons, which is comparable to the total duration of DIEP flap breast reconstruction cases 39,40 . It is well-documented that free flap breast reconstruction often requires access to microsurgical expertise, longer hospital stay, and additional resources for inpatient floor or intensive care unit flap monitoring 41–43 .…”
Section: Discussionmentioning
confidence: 76%
“…8 25 26 27 28 Synergistic co-surgery models have been demonstrated as a safe method of reducing operative time in autologous breast reconstruction. 8 25 26 Rigorous process analysis incites continual assessments in improving surgical flow and employment of hidden time. 8 29 30…”
Section: Discussionmentioning
confidence: 99%
“…The flaws of the RVU system have been shown to influence surgical decisions across specialties, affecting patient outcomes of all disciplines. 8,[20][21][22][23] These concerns may be reflected in the popularity of carve-outs (reimbursement agreements that exceed the gross recipient indicated by Medicare) and use of Healthcare Common Procedure Coding System codes in microsurgical breast reconstruction. Carve-outs, however, may facilitate additional inequities in reimbursement.…”
Section: Discussionmentioning
confidence: 99%
“…This allowed us to identify operative times for individual CPT codes and avoid the confounding effects of co-surgery cases, which are common in plastic surgery. Data supporting this decision have been presented by Issa et al, 8 who showed statistically significant reductions in operative times performing breast free flaps in a planned staged fashion rather than immediate.…”
Section: Case Selectionmentioning
confidence: 92%